Anti-Tumour Effects of High Affinity L-type Amino Acid Transporter1 Inhibitors on Human Pancreatic Adencarcinoma Cells (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: a system L transporter L-type amino acid transporter 1 (LAT1) is upregulated to support tumor cell growth in malignant tumor. Objective: The purpose of the present study was to investigate the growth inhibition and [14C] L-leucine transport in human pancreatic adenocarcinoma cells MAIPaCa-2 and BXPC3. Methodology: This animal study was carried out in Japan. The in vitro growth inhibition study was performed by using KYT0351 and KYT0353 which inhibited the tumor cell growth in dose dependent manner and uptake of [14C] L-leucine by MIAPaCa-2 and BXPC3 cells was Na+- independent and was strongly inhibited by KYT0351 and KYT0353. The in vivo tumor growth inhibition was also carried out by intra tumor injection of KYT0351 and KYT0353 at the concentration of 2.6mM of each on both the MIAPaCa-2 and BXPC3 nude mice tumor. Result: In a subsequent survival study with the intra peritoneal injection of ascites mice model, control mice had a mean life span of 20 ± 4.30 days and 21 ± 5 days in MIAPaCa-2 and BXPC3 cells respectively, whereas the intraperitoneal injection of 10mg/kg twice daily of KYT0351 and KYT0353 group had improved survival (mean life span 28.4 ± 8.5 and 34.4 ± 9.86 days, 26 ±4.52 and 31.8 ± 7.62 days respectively in MIAPaCa-2 and BXPC3 cells). Kaplan-Meier survival data of nude mice treated with KYT0351 and KYT0353 were significant. To study the mechanism of growth inhibition we investigated the MIB-1 proliferation assay and TUNEL assay. Significantly less MIB-1 staining and more apoptotic nuclei was detected in tumors treated with KYT0351 and KYT0353 in both MIAPaCa-2 and BXPC3 cells compared with saline treated group. Conclusion: In conclusion both the KYT0351 and KYT0353 is a potent LAT1-specific inhibitor and LAT1 could be one of the molecular target in pancreatic adenocarcinoma therapy. Journal of National Institute of Neurosciences Bangladesh, 2016;2(2): 55-68